Sirolimus alternative to blood transfusion as a life saver in blue rubber bleb nevus syndrome: A case report. Issue 8 (February 2018) - Wang, Ke-Ling; Ma, Shu-Fang; Pang, Ling-Yu; Zhang, Meng-Na; Hu, Lin-Yan; Liu, Meng-Jia; Zou, Li-Ping
Abstract: Rationale: Blue rubber bleb nevus syndrome (BRBNS) is a rare disease characterized by multiple venous malformations. The gastrointestinal bleeding and secondary iron deficiency anemia are the most common complications. There are currently no effective treatments for BRBNS. Here, we report a case of successful treatment with a small dose of sirolimus of a BRBN patient with a de novo gene mutation. Patient concerns: A 12-year-old female was admitted to our hospital with multiple hemangiomas for 12 years. The patient often displayed melena; she recently received transfusion of 2 units of red blood cells once every 2 weeks. Multiple fist-sized hemangiomas were piled up on both sides and back of the neck, and were also noted on the arms, legs, chest, back, and on the tip of the tongue. The laboratory findings demonstrated severe anemia. Blood sample sequencing detected a heterozygous de novo mutation c.2545C > Tin the TEK gene. Diagnoses: Based on these findings, final diagnosis of Blue rubber bleb nevus syndrome (BRBNS) was made. Interventions: After the diagnosis, low-dose sirolimus was orally administered. Outcomes: The patient's hemoglobin was increased after treatment with sirolimus for 1 month. Since the initial treatment with sirolimus, she had not received any blood transfusions. The skin and mucosal hemangioma decreased significantly, and new digestive tract hemorrhage, muscle hematoma, or adverse drug reactions were not observed. Lessons: we report a case of a mutation in exon 15 of the TEK gene leading to BRBN. It was successfully treated with a small dose of sirolimus as an alternative to blood transfusion in order to save the of BRBN patient's life.